WHAT DETERMINES ISLAMIC PERFORMANCE RATIO OF ISLAMIC BANKING IN INDONESIA? AN ANALYSIS USING FINANCING TO DEPOSIT RATIO AS MODERATOR - Lucky Nugroho; Ahmad Badawi; Erik Nugraha; Yananto Mihadi Putra (Share: Jurnal Ekonomi dan Keuangan Islam, 2021)
The measurement of Islamic banking performance should differ from the indicators used in their conventional counterparts. Therefore, this study analyzes the performance of Islamic baking in Indonesia using the Islamic Performance Ratio (IPR) variable. Spesifcillay, this study aims to examine the influence of Asset Growth and Non-Performing Financing (NPF) on the IPR using Financing to Deposit Ratio (FDR) as moderator. Data for this study were gathered from seven Islamic Commercial Banks from 2012 to 2018 with 49 observations. They were analyzed using the quantitative approach by employing SPSS software. The findings show that the quality of financing has a negative but significant effect on the IPR. Meanwhile, asset growth does not have a significant direct effect on the IPR. When FDR was inserted as moderator, it showed a significant effect of asset growth on IPR. The theoretical implication of this research shows that Islamic banks' performance is shown from the growth of assets but must be supported by other variables such as the quality of financing (NPF) and must also be accompanied by good financing disbursement capability (FDR). In addition, the managerial implication of this research is that the measurement of indicators for Islamic banks should be equipped with performance indicators under the operational principles of Islamic banks, such as the Islamic Performance Ratio (IPR).======================================================================================================== ABSTRAK – Determinan yang Mempengaruhi Islamic Performance Ratio Perbankan Syariah di Indonesia: Suatu Analisis Menggunakan Financing to Deposit Ratio sebagai Moderator. Pengukuran kinerja perbankan syariah seharusnya menggunakan parameter yang berbeda dari perbankan konvensional. Oleh karena itu, article bertujuan untuk menganalisis kinerja perbankan syariah di Indonesia menggunakan variabel Islamic Performance Ratio (IPR). Secara khusus, artikel ini bermaksud untuk menguji pengaruh variabel pertumbuhan aset dan pembiayaan bermasalah (NPF) terhadap IPR dengan menggunakan Financing to Deposit Ratio (FDR) sebagai variabel moderator. Data-data untuk kajian dikumpulkan dari tujuh bank umum syariah dari 2012 sampai 2018 dengan 49 observasi yang kemudian dianalisis secara kuantitatif dengan software SPSS. Hasil kajian menunjukkan bahwa kualitas pembiayaan memiliki pengaruh negatif tapi signifikan terhadap IPR. Sedangkan pertumbuhan aset tidak berpengaruh signifikan secara langsung terhadap IPR. Ketika FDR dimasukkan sebagai moderasi, pertumbuhan berpengaruh secara signifikan terhadap IPR. Implikasi teoritikal dari penelitian ini menunjukkan bahwa kinerja bank syariah tidak hanya ditunjukkan dari pertumbuhan aset saja, akan tetapi harus didukung dengan variabel lainnya seperti kualitas pembiayaan (NPF) dan juga harus disertai dengan kemampuan penyaluran pembiayaan yang baik (FDR). Selain itu, implikasi manajerial dari penelitian ini adalah pengukuran indikator dari bank syariah sebaknya dilengkapi dengan indikator kinerja yang sesuai dengan prinsip operasional dari bank syariah seperti Islamic Performance Ratio (IPR).